In Vivo study of intra-articular Tualang honey formulation as a potential alternative to Synvisc® in an osteoarthritic rabbit model - Abd. Rahim, Nour El Huda; Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Mohamad Amri, Nur Fathonah; Ibrahim, Mohd Zulfadzli; Mohamed, Farahidah; Abu Hassan, Salmah Anim; Nasuruddin, Muhammad Haidar (The Malaysian Orthopaedic Journal (MOJ), 2026)
Introduction: Osteoarthritis (OA) is a degenerative joint disorder characterised by cartilage degradation and inflammation. This study evaluates the efficacy of Tualang Honey Formulation (THF) (Patent no. MY-179303-A), a natural-based formulation tested for biocompatibility and toxicity, compared to Synvisc, a conventional hyaluronic acid injection, in managing OA in vivo using an animal model. Materials and methods: Twenty-eight New Zealand White Rabbits (NZWR) were operated to surgically induce OA and divided into three groups: sham group (n=1), THF-treated group (n=3) and Synvisc-treated group (n=3). Treatments were administered intra-articularly three weeks post-surgery. Radiographic assessments were performed at 3, 6, 12, and 24 weeks. Histological analyses at 24 weeks utilised MassonGoldner trichrome staining. Results: In the sham group, severe cartilage loss, thinning, and thickened subchondral bone were observed, reflecting progressive OA. Radiographically, both THF and Synvisc groups demonstrated improved joint space and reduced subchondral sclerosis. At six weeks, the THF and Synvisc groups exhibited improvements from three weeks. At 12 weeks, the THF group demonstrated better joint space preservation, while outcomes were comparable at 24 weeks. Histologically, the THF group displayed thicker articular surfaces with signs of bone remodelling with better cartilage preservation. In contrast, Synvisc-treated joints displayed thinner, irregular cartilage and subchondral bone changes, suggestive of potential bone cyst formation. Conclusion: THF is equally effective as Synvisc in reducing OA progression while showing additional benefits in cartilage preservation and bone remodelling. As a natural and local product, THF represents a promising alternative viscosupplement for OA management, warranting further clinical validation.